Israel : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper reviews the housing market in Israel. Property prices in Israel are currently about 25 percent above their equilibrium value, owing largely to low mortgage interest rates and supply shortages. Nominal housing prices have risen by 80 percent since 2007. In response to the global financial and euro area crises, the Bank of Israel engaged in two rounds of monetary easing. The monetary stimulus supported economic growth, but it also boosted demand in the mortgage and housing markets. The risk of a sharp correction in housing prices, while mitigated by the supply shortages, remains a concern and could have important macro-financial implications. To contain such risks, macroprudential policies should be further tightened. At the same time, concerted efforts should be made to alleviate supply-side constraints.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet